Disturb mitochondrial associated proteostasis: Neurodegeneration and imperfect ageing - Jagtap, Yuvraj Anandrao; Kumar, Prashant; Kinger, Sumit; Dubey, Ankur Rakesh; Choudhary, Akash; Gutti, Ravi Kumar; Singh, Sarika; Jha, Hem Chandra; Poluri, Krishna Mohan; Mishra, Amit (Frontiers in Cell and Developmental Biology, 2023)
The disturbance in mitochondrial functions and homeostasis are the major features of neuron degenerative conditions, like Parkinson’s disease, Amyotrophic Lateral Sclerosis, and Alzheimer’s disease, along with protein misfolding. The aberrantly folded proteins are known to link with impaired mitochondrial pathways, further contributing to disease pathogenesis. Despite their central significance, the implications of mitochondrial homeostasis disruption on other organelles and cellular processes remain insufficiently explored. Here, we have reviewed the dysfunction in mitochondrial physiology, under neuron degenerating conditions. The disease misfolded proteins impact quality control mechanisms of mitochondria, such as fission, fusion, mitophagy, and proteasomal clearance, to the detriment of neuron. The adversely affected mitochondrial functional roles, like oxidative phosphorylation, calcium homeostasis, and biomolecule synthesis as well as its axes and contacts with endoplasmic reticulum and lysosomes are also discussed. Mitochondria sense and respond to multiple cytotoxic stress to make cell adapt and survive, though chronic dysfunction leads to cell death. Mitochondria and their proteins can be candidates for biomarkers and therapeutic targets. Investigation of internetworking between mitochondria and neurodegeneration proteins can enhance our holistic understanding of such conditions and help in designing more targeted therapies.